ANALISIS KUALITAS PELAYANAN UJI KIR TERHADAP KEPUASAN MASYARAKAT PENGGUNA JASA KIR DI DINAS PERHUBUNGAN KOTA KEDIRI - Santoso, Agung (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
Public services organized by public organizations are one manifestation of functions of the state government apparatus as civil servants. Public services are intended to prosper the community. The condition of people who experience dynamic development, the better level of community life, resulting in people becoming more aware of what their rights and obligations are as citizens in living in the community, proposing their demands, desires, and aspirations to the government. The purpose of this study are as follows: 1) To determine the service quality of KIR test at the Department of Transportation (Dishub) of Kediri City? 2) To find out the satisfaction of KIR service users in the Department of Transportation (Dishub) of Kediri City?, 3) To analyze the influence Kir test service quality to the satisfaction of KIR service users in the Kediri City Transportation Agency (Dishub)? This study uses quantitative research designs. This study consists of two variables, namely the independent variable of this study is the quality of service while the dependent variable of the study is the satisfaction of the users of mobile vehicle testing services, data collection by distributing questionnaires to respondents. Based on the results of the research. The following conclusions can be drawn: 1) Based on the results of the investigation it has been proven that the quality of service of the KIR test at the Kediri City Transportation Agency (Dishub) is good, service employees, facilities and tools the support used in the test is complete and modern. 2) Based on the results of the analysis it has been proven that the level of satisfaction of KIR service users in the Kediri City Transportation Agency (Dishub) is quite high. 3) There is a significant effect of service quality variables on community satisfaction of test service users in the city of Kediri, service quality variables have an impact of 78.6% on the achievement of the service user community.